FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN LEMBAGA KEUANGAN SYARI’AH BENGKULU TERHADAP ALUMNI JURUSAN EKONOMI ISLAM IAIN BENGKULU DALAM REKRUITMEN TENAGA KERJA - Isnaini, Desi (Institut Agama Islam Bengkulu, 2017)
This paper is motivated by the problems of the development of sharia financial institutions are growing rapidly in the city of Bengkulu, impact on the needs of human resources are not small, but after the author observe very little of the Department of Islamic Economics or Muamalah Department who work in Islamic financial institutions. The type of research used is the type of qualitative research, aiming to describe the systematic and factual, by examining the phenomenon of emperis in detail. The results of this study found that there is the same recognition for graduates of the Department of Islamic Economics and other Departments, and there are no exceptions for Islamic Economics majors in taking the test in Islamic financial institutions both banks and non-banks, because all of these agencies accept applications from all Majors. There are two factors that influence the level of confidence of sharia financial institutions bengkulu to graduates majoring in Islamic Economics IAIN Bengkulu, that is: a). External Factors, that is: Curriculum, Index of achievement komulatif, Accreditation of study program. b). Internal Factors ,that is: Insights general knowledge, keIslaman, kesyari'ahan, Soul marketing and managerial, professional and confident, advanced and developing mindset, able to utilize Technology, Good Attitude and Performance, Integrity and high spirit. While the competence must be owned by a graduate of the Department of Islamic Economics is Cognitive Competence, ie science and skills, Personality and Attitude Competencies, Social and Communication Competencies, Professional Competencies.Keywords: Rekruitmen Tenaga Kerja